The bedrock topography of Starbuck Glacier, Antarctic Peninsula, as determined by radio-echo soundings and flow modeling - Farinotti, Daniel; id_orcid:0 000-0003-3417-4570; King, Edward C.; Albrecht, Anika; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Gudmundsson, Gudmundur H. (Annals of Glaciology, 2014)
ISSN:0260-3055 ISSN:1727-5644